Thermodynamic synthesis of solution processable ladder polymers - Lee, Jongbok (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
The synthesis of a carbazole-derived, well-defined ladder polymer was achieved under thermodynamic control by employing reversible ring-closing olefin metathesis. This unique approach featured mild conditions and excellent efficiency, affording the ladder polymer backbone with minimum levels of unreacted defects. Rigorous NMR analysis on a (13)C isotope-enriched product revealed that the main-chain contained less than 1% of unreacted precursory vinyl groups. The rigid conformation of the ladder-type backbone was confirmed by photophysical analysis, while the extended rod-like structure was visualized under scanning tunneling microscope. Excellent solubility of this polymer in common organic solvents allowed for feasible processing of thin films using solution-casting techniques. Atomic force microscopy and grazing incident X-ray scattering revealed a uniform and amorphous morphology of these films, in sharp contrast to the polycrystalline thin films of its small molecular counterpart.